Gümrük Birliğinin dayanıklı tüketim mallarına etkisi - Yıldız, Canan (My University, 2000)
The struggle of Turkey with European Union during over thirty-five years has been concluded with Duty Union and limited integration. From 1.1.1996 on, duty tasks and quotas were cancelled in industrial products and processed soil products between the Turkey and European Union Countries and Turkey has started to apply the duty task ratio of European Union to third country. Turkey completed the laws of adaptation about patent rights, state assistance in export, the standards in foreign exchange and management of quota. Since having Duty Union, the industry of durable consumer goods were affected like as other sectors. In 1995, increasing about exporting amount of industrial product affected the manufacturing industry positively and the quantity of importing of manufacturing industry was increased. The duty union which we are included is a supported and improved component for Turkish industry. To get more profit is most important thing in the increased competition and forces the firm to work productively. Cost, productive, profit and assistance of state are basic factors that determine the power of competition. In last 50 years, Turkey has changed its appearance. The changing in life style and culture have affected manufacturing industry as well. The manufacturing industry which is controlled by three large group that are Arcelik, Bosch-Siemens-Profilo, Merloni has made it` s preparedness clear about quality of manufacture, productivity, and potential demand. Manufacturing industry which has specialities of European-styled manufacture, usage of modern technology, quality of researching, qualified person, high adaptation, strategical geographical location, and having strong mark has some weak point. Because of high cost of supplies and energy, some troubles will be held. If the troubles would not eliminate in a sort time it is obvious that the capable of competition will be weak.
Keywords: Dayanıklı tüketim malları; Gümrük birlikleri